2006
DOI: 10.1111/j.1365-2141.2005.05945.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of asparagine synthetase in blasts from children and adults with acute lymphoblastic leukaemia

Abstract: l-asparaginase (l-asp) is an important component in the treatment of childhood acute lymphoblastic leukaemia (ALL).Recently the assumption that leukaemic cells are sensitive to l-asp because of a relative lack of asparagine synthetase (AS) has been questioned (Stams et al, 2003;Krejci et al, 2004). Using a real-time quantitative reverse transcription polymerase chain reaction (RQ RT-PCR) assay with transcription binding protein IID/TATA (TBP) as the internal control we provide evidence to support the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 9 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…Apart from this well-recognized effect of L-asparaginase in children ALL, recently, a beneficial effect of L-asparaginase on patients with AML, particular on M5 subtype (FAB classification), has also been proposed. Generally, studies on sensitivity to L-asparaginase in leukemia cells and primary leukemic cells focused on the cellular expression of ASNS, and enzyme activity with the test of in vitro resistance to L-asparaginase [5,6,[11][12][13][14][15][16][17][18][19] . Whereas, little research effort has been directed at other features of ASNS, such as its intracellular localization in the relation with chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this well-recognized effect of L-asparaginase in children ALL, recently, a beneficial effect of L-asparaginase on patients with AML, particular on M5 subtype (FAB classification), has also been proposed. Generally, studies on sensitivity to L-asparaginase in leukemia cells and primary leukemic cells focused on the cellular expression of ASNS, and enzyme activity with the test of in vitro resistance to L-asparaginase [5,6,[11][12][13][14][15][16][17][18][19] . Whereas, little research effort has been directed at other features of ASNS, such as its intracellular localization in the relation with chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…11 One prediction of this model is that increased levels of cellular ASNS are the cause of ASNaseresistance in lymphoblasts because sufficient asparagine is made available as a result of increased intracellular asparagine biosynthesis. 8,12,13 Support for this hypothesis has come from studies employing transformed cell lines. For example, in vitro studies with U937 cells demonstrated that ASNase-sensitive cells can be made resistant by persistent exposure to increasing levels of sublethal doses of the drug, and constitutive expression of ASNS in a human ALL cell line (MOLT-4) conferred ASNase-resistance onto sensitive parental cells.…”
Section: Introductionmentioning
confidence: 89%
“…ASNase catalyzes the hydrolysis of amino acid asparagine to aspartic acid and ammonia, exploiting an Achilles heel in the leukemic lymphoblast, low or absent levels of asparagine synthetase (ASNS) (2). The potency of the drug to induce cell death is a consequence of asparagine starvation and is strength-ened by its intrinsic glutaminase activity, which lowers the levels of glutamine, an essential substrate in the synthesis of asparagine by ASNS (glutamine + aspartate / glutamate + asparagine) (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%